Analysis of clinical diagnosis of patient presenting to emergency of Patan Hospital - Marasini, Pawan; Shrestha, Grishma; Gurung, Sunita; Ruit, Sagar; Koirala, Nitish; Khadga, Mukesh; Khadka, Samir (Journal of General Practice and Emergency Medicine of Nepal, 2015)
Introduction: Emergency department sees variety of patients with different acuity. We are conducting this study to analyze the clinical diagnosis of patient presenting to emergency department. This can help to plan protocols and prepare resources for the better management.Methods: This is a cross sectional study that was carried out from June 2014 to May 2015. Age, sex, primary presenting complaint, secondary presenting complaint, primary and secondary discharge diagnosis was recorded.A register was maintained and data was entered upon discharge of patient and also during the rounds . Data was entered in google drive and verified every month. Proportion was used for analysis of data.Results: Total data collected in emergency department was 3,815which is 19.93% of total ER visits. Out of this, male were 1,996 (52.3%) and female were 1,809 (47.8%). On categorizing by age, neonates were 20 (0.5%), infants 73 (1.9%), under five year 295 (7.7%), pediatric – six years to fourteen years 265 (6.9%), adult- fifteen to sixty five years – 2,643 (69.3%) and geriatric- more than sixty five years 519 (13.6%). Among the top five presenting complains in ER, the most common presenting symptom was pain abdomen(21.86%) in which Gastritis(33.45%) was the commonest cause, followed by fever(15.54%) which was caused mostly due to Pneumonia(28.42%) then trauma(11.92%) which had soft tissue injury(32.31%) as its main cause followed by shortness of breath (9.1%) having COPD(52.44%) as its main cause and lastly, loose stool(5.69%) which had Acute gastroenteritis(11.98%) as its main cause.Conclusions: Pain abdomen is the most common cause of patient presenting to emergency out of which gastritis is the most common.